DETERMINACIÓN Y DESIGNACIÓN DE APOYOS DE LAS PERSONAS CON DISCAPACIDAD. A PROPÓSITO DE LA MODIFICACIÓN DEL CÓDIGO CIVIL POR EL DECRETO LEGISLATIVO N.º 1384 - Lescano Feria, Patricia Anahí (2022)
With the publication of Legislative Decree No. 1384, Legislative decree that recognizes and regulates the legal capacity of people with disabilities under equal conditions – on September 4, 2018, a series of articles of the Civil Code that affect the issue of the capacity. The objective was to promote the legal capacity of people with disabilities. For this reason, said persons will no longer be subjected to an interdiction process; they will be able to make their own decisions and carry out actions that they could not before. If perhaps they cannot develop certain acts, the supports and safeguards can be configured. These in no case substitute the will. The objective of this article is to focus, precisely, on said supports: their definition and determination; as well as its designation. The Civil Code refers to some of these points, but it is necessary to analyze each one of them to understand the figure and give coherent and fair responses to a vulnerable group that needs the attention of the legislator and society.